Conservation of Greater Sage-grouse: challenges managing a landscape scale species - Stiver, San, speaker; Riley, Terry, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Greater Sage-grouse are a western North American plains grouse that had a potential pre-European settlement distribution of approximately 1,200,483 km2, spanning 12 US states and three Canadian provinces. That distribution has declined to < 668,412 km2 in 11 states and two Canadian provinces. The Greater Sage-grouse was determined by the U.S. Fish and Wildlife Service in 2010 to warrant protection under the Endangered Species Act, but were precluded because of higher conservation priorities. Concern for the species, by a host of conservation entities lead to a comprehensive range-wide conservation strategy which includes conservation efforts, monitoring, adaptive management, research and technology, communication and funding components. The strategy was based upon the need to manage Greater Sage-grouse from a range-wide perspective, spanning multiple jurisdictions and coordinating conservation efforts on a landscape scale. We will explore the biological, economic, temporal, and political challenges of managing this species and the sagebrush biome. Sage-grouse are a sagebrush obligate species; depending upon the plant for many of its life functions. Sage-grouse as individuals or populations require large tracts of sagebrush, often spanning jurisdictions and land ownership to meet their needs. Sagebrush is a very slow growing shrub that is vulnerable to wildfire and disturbance. Some species of sagebrush require decades to reach a preferred age class for sage-grouse. Resources important to Western States will necessarily be impacted by an ESA listing and the prospect of an ESA listing has the attention of politicians from the Administration, the Senate and House, Governors, State Legislatures and County Commissions.
Moderator: Terry Riley.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses